ELIMINATION OF NON-TARIFF BARRIERS OF TRADE IN GOODS IN THE ASEAN REGION: WILL IT EVER WORK? - Wiko, Garuda; Kinanti, Fatma Muthia (Jurnal Hukum & Pembangunan, 2021)
Within the framework of the ASEAN Economic Community (AEC), there is a mandate to promote trade liberalization with the aim of increasing intra-ASEAN trade. The realization of the AEC includes the existence of the free flow of goods, services and investments within the ASEAN region. In terms of trade in goods, the regulations within the AEC framework are intended to promote the establishment of single markets and production bases in the ASEAN region that does not only require the elimination of tariff barriers, but also non-tariff barriers.This article concludethat the NTB Regulations in the AEC 2015 are not very well implemented proven by the increase amount of NTMs imposed by ASEAN countries. It was found that several initiatives have been formulated in the AEC Blueprint 2025 in order to further eliminate non-tarrif barriers.